Assessing and managing demersal fisheries in Sunda Strait: Bio-economic modelling. Issue 1 (October 2021) - Lindawati, L; Mardyani, Y; Yanti, N D; Boer, M
Abstract: Management of demersal fisheries in Sunda Strait has recently decreased productivity, especially Sulphur goatfish (Upeneus spp.), one type of demersal fish with economic value. The increasing demand for demersal fisheries causes high pressure on the existence of these resources due to the increasing intensity of capture. Based on these conditions, the study aims to determine the utilization level of demersal fisheries (Sulphur goatfish) in the Sunda Strait. The catch and fishing trips data were collected from Labuan Coastal Fishery Port (PPP), Pandeglang Regency, Banten, Fisheries Office of Pandeglang Regency, and Fisheries and Marine Agency of Banten Province during 2008-2017. Surplus production models are used to estimate the biological parameters of Sulphur goatfish. The regression and the modeling show that the CYP is the most suitable model based on the highest? ! (0.74) and the values of the biological parameters consisted of the intrinsic growth rate (0.7670), the catchability coefficient (0.0002454), and the carrying capacity (5, 914.06 tons per year). The bio-economic analysis shows that utilization of Sulphur goatfish (Upeneus spp.) have experienced biological and economic overfishing, as shown on the average of the actual catch of 1, 734.84 tonnes/year, above the MSY and MEY values of 1, 133 tonnes/year, and the actual effort of 4, 198.81 trips/year, which is far above the effort of MSY and MEY in the range of 1, 500 trips/year. Consequently, the management strategies that can be suggested are regulating catch effort, fishing time, and mesh size, as well as improving cooperation among stakeholders, thus creating sustainable fisheries management.